Reccurent apthous with psychological stress predisposing factor – a case report - Liftia Layyinatus Syifa; Rochman Mujayanto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Aphthous stomatitis (RAS) is a painful recurrent inflammatory process of the oral mucosa. Clinical features of inflammation in aphthous stomatitis in the form of ulcers on the oral mucosa can be single or multiple and have no relationship with a systemic disease. The etiopathogenesis of aphthous stomatitis is several predisposing factors in the manifestation of the oral cavity. This article presents case reports on RAS patients with stress-predisposing factors. Case: In October 2019, A 52-year-old female patient came to RSIGM complaining of canker sores in several places in her oral cavity, namely on the right inner lip, left inner lip, floor of the mouth, and under the tongue. The patient has felt this condition for the last 2 years, but the canker sores have disappeared and reappeared. The Miller and Smith test showed that the score is 42. We diagnosed the RAS patients with stress-predisposing factors. Case Management: The patient was given oral methylprednisolone and becomzed tablet and counseling management stress. Conclusion: cases of recurrent aphthous stomatitis are caused by psychological stress which can cause recurrent ulcers in the oral cavity. Eliminating stress-causing variables is one of the key therapies for these diseases. some patients need counseling with experts in stress management in addition to systemic treatment according to the symptoms felt by the patient